Gaffelbandsskador - Staaf, Susanna (2007)
Suspensory ligament injuries are a common cause of lameness among sport horses. These injuries are expensive due to slow healing, extensive convalescence and high risk of recurrence. The prognosis has been reported to be everything from good to guarded depending on the size of the lesion and the location within the suspensory ligament. The purpose of this study was to determine how different factors such as age, use, and location of the lesion are associated with the final outcome after a suspensory ligament injury.